2015
DOI: 10.1021/acsnano.5b04592
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Ferroelectric Memory Circuit Using Black Phosphorus Nanosheet-Based Field-Effect Transistors with P(VDF-TrFE) Polymer

Abstract: Two-dimensional van der Waals (2D vdWs) materials are a class of new materials that can provide important resources for future electronics and materials sciences due to their unique physical properties. Among 2D vdWs materials, black phosphorus (BP) has exhibited significant potential for use in electronic and optoelectronic applications because of its allotropic properties, high mobility, and direct and narrow band gap. Here, we demonstrate a few-layered BP-based nonvolatile memory transistor with a poly(viny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 40 publications
3
88
0
2
Order By: Relevance
“…The high polarization field and dielectric constants of ferroelectric materials produce very efficient gating effects in 2D materials, modulating charge density, and all physical properties over wide range of applied voltages. Based on this, many novel device functionalities and architectures have been recently proposed including ferroelectric 2D memory devices, highly sensitive photo‐transistors, low‐power field‐effect transistors enabled by high‐κ ferroelectrics . Most of the reports in this research area have focused on ferroelectric FET structures (FeFET) where a ferroelectric layer serves as gate dielectric material .…”
Section: Other Emerging Nvm Cells Based On Grmsmentioning
confidence: 99%
“…The high polarization field and dielectric constants of ferroelectric materials produce very efficient gating effects in 2D materials, modulating charge density, and all physical properties over wide range of applied voltages. Based on this, many novel device functionalities and architectures have been recently proposed including ferroelectric 2D memory devices, highly sensitive photo‐transistors, low‐power field‐effect transistors enabled by high‐κ ferroelectrics . Most of the reports in this research area have focused on ferroelectric FET structures (FeFET) where a ferroelectric layer serves as gate dielectric material .…”
Section: Other Emerging Nvm Cells Based On Grmsmentioning
confidence: 99%
“…Several earlier studies have reported on the combination of ferroelectrics and 2D materials, but most applications have been in memory devices and photodetectors. 18,[24][25][26][27][28] In addition, F. A. McGuire et al achieved an Fe2DFET with a sub-60 mV/dec SS, but their device was based on the MFMIS structure. 29 In addition to poly(vinylidene difluoridetrifluoroethylene) (P(VDF-TrFE)), hafnium zirconium oxide (HZO) has recently emerged as an environmentally friendly ferroelectric material.…”
Section: Introductionmentioning
confidence: 99%
“…The device with monolayer MoS 2 possesses a mobility as high as 220 cm 2 V −1 s −1 , a subthreshold swing of 300 mV/decade, and a~5 × 10 3 write and erase current ratio [94]. The memory inverters also show a good performance and high output voltage efficiency [95].…”
Section: Nonvolatile Memory and Data Storagementioning
confidence: 99%